Assement of the quality in the medicine faculty: The quality control or the continuos task - Piscoya Arbañil, José (1995)
Nowadays, the University remains to be a place of reflexion, nevertheless inside the historical process, it should play a role as an organization of services because, as an institution, it manages academically information to render individual and general services to the country and community. It is required a managerial and not a mere administrative University which focus its attention toward the total quality as well as the education of executive students and toward the re-estructuration of their roles. The managerial University centred in the total quality brings important benefits to the University as an Institution. This makes the University be able to continue with the fulfillment of its aims and direct at the future without forgetting that the University, as an Institution of spirit, as a place of dialogue, and as a place of entertainment of the history, become in a "cold factory" of professionals, technical services and even of different products. In this review, we scheduled the principles developped in the Faculty of Medicine from San Fernando in cosidering their true potentials in order to make the organizational and aducational changes, and incorporating them into plans as an educative and pedagogical philosophy typical of our faculty in order to continue to be a leader in medicine.